(untitled) (The Research of Medical Science Review, 2025)
Introduction: Peripheral vascular disease (PVD) is significantly linked to systemic atherosclerosis, which elevates the risk of carotid artery stenosis (CAS) and subsequent cerebrovascular incidents. Timely intervention through early detection of significant CAS in patients with PVD can enhance outcomes. Objectives: To determine the frequency of significant carotid artery stenosis in patients presenting with symptomatic peripheral vascular disease. Subjects & Methods: This cross-sectional study was conducted at the Department of Surgery, Division of Vascular Surgery, Foundation University School of Health Sciences, Rawalpindi from January-April, 2025. 170 symptomatic PVD patients of both genders having age between 18 to 80 years were enrolled for this study. Following clinical assessment and Doppler confirmation, a bilateral carotid ultrasound was conducted to identify severe stenosis on the basis of MCA-PSV. Significant CAS labelled as positive if there is ≥50% of stenosis as per SRUCC criteria. Data was analyzed using SPSS 23.0, with results presented as frequencies, percentages, and means ± SD. Stratification was performed for study confounders, and a post-stratification Chi-square test was utilized, with a p-value of ≤ 0.05 deemed significant. Results. Study was female dominant 117 (68.8%) and most patients were aged 50–60 years (n=76; 44.7%). Cumulative mean age of the study population was 55.64±10.20 years. Significant carotid artery stenosis was found in 27 (15.9%) patients, while 143 (84.1%) had no significant stenosis. We found no statistically significant association among significant carotid artery stenosis and gender, age, BMI, duration of symptoms, or clinical presentation (p-values > 0.05). Conclusions: A significant proportion of individuals with PVD demonstrated notable CAS. Although the stratified analysis did not reveal statistically significant relationships, trends suggest an increased risk among females, those with obesity, and patients with advanced limb ischemia.